Bahasa, Identitas, dan Iman: Pergeseran Bahasa Melayu dalam Bayang-Bayang Ideologi Agama di Kota Duri - Kasmuri, Kasmuri; Usman, Usman; Hanafi, Imam (HUMANIKA, 2025)
This research explores the phenomenon of a Malay language shift in Duri City, Bengkalis Regency, within a multi-ethnic and multi-religious society. This shift is driven not only by demographic changes, such as the large-scale migration of Minangkabau, Batak, and Javanese communities, but also by ideological dynamics embedded in the language itself. Once a symbol of Malay-Islamic culture and civilization, the Malay language has increasingly become associated with specific religious identities. This exclusivist framing led to resistance from non-Muslim groups. Using a qualitative-descriptive method and critical sociolinguistic approach, this study demonstrates that the Malay language has lost its inclusive communicative function. Instead, it has evolved into a symbolic marker that generates social boundaries and constructs identity. Drawing on theories of language ideology (Irvine & Gal, 2000) and linguistic capital (Bourdieu), this research finds that language choice in Duri’s public space is no longer merely pragmatic. It functions as a means of representing and symbolizing resistance to perceived cultural domination. This study recommends a reorientation of language ideology and the implementation of policies to revitalize the Malay language as a symbol of inclusive culture—one that transcends religious and ethnic divides.